Platelets and plasma stimulate sheep rotator cuff tendon tenocytes when cultured in an extracellular matrix scaffold. Issue 4 (8th October 2015) - Kelly, Brian A.; Proffen, Benedikt L.; Haslauer, Carla M.; Murray, Martha M.
ABSTRACT: The addition of platelet‐rich plasma (PRP) to rotator cuff repair has not translated into improved outcomes after surgery. However, recent work stimulating ligament healing has demonstrated improved outcomes when PRP or whole blood is combined with an extracellular matrix carrier. The objective of this study was to evaluate the effect of three components of blood (plasma, platelets, and macrophages) on the in vitro activity of ovine rotator cuff cells cultured in an extracellular matrix environment. Tenocytes were obtained from six ovine infraspinatus tendons and cultured over 14 days in an extracellular matrix scaffold with the following additives: (1) plasma (PPP), (2) plasma and platelets (PAP), (3) plasma and macrophages (PPPM), (4) plasma, platelets and macrophages (PAPM), (5) phosphate buffered saline (PBS), and (6) PBS with macrophages (PBSM). Assays measuring cellular metabolism (AlamarBlue), proliferation (Quantitative DNA assay), synthesis of collagen and cytokines (SIRCOL, TNF‐α and IL‐10 ELISA, and MMP assay), and collagen gene expression (qPCR) were performed over the duration of the experiment, as well as histology at the conclusion. Plasma was found to stimulate cell attachment and spreading on the scaffold, as well as cellular proliferation. Platelets also stimulated cell proliferation, cellular metabolism, transition of cells to a myofibroblast phenotype, and contraction of the scaffolds. The addition of macrophages did not have any significant effect on the sheep rotator cuff cells in vitro. In vivo studies are needed to determine whether these changes in cellular function will translate into improved tendon healing. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:623–629, 2016.